Molecular hydrogen at zabs=1.973 toward Q 0013−004: dust depletion pattern in damped Lyman α systems - Petitjean, Patrick; Srianand, R.; Ledoux, Cédric (Monthly notices of the Royal Astronomical Society, 2002)
We study the dust depletion pattern in eight well-separated components of the zabs=1.973, log N(H i)=20.83, damped Lyman α system towards Q 0013−004, four of which have detectable H2 absorption. The apparent correlation between the abundance ratios [Fe/S] and [Si/S] in the components indicates that the abundance pattern is indeed as a result of dust-depletion. In particular, we find evidence for depletion similar to what is observed in cold gas of the Galactic disc ([Fe/Zn]=-1.59, [Fe/S]=-1.74, [Zn/S]=-0.15, [Si/S]=-0.85) in one of the weakest components in which molecular hydrogen is detected with log N(H2)∼16.5. This is the first time such a large depletion is seen in a DLA system. Extinction due to this component is negligible owing to small total H i column density, log N(H i)⩽19.4. This observation supports the possibility that current samples of DLA systems might be biased against the presence of cold and dusty gas along the line of sight. The overall metallicities of this peculiar DLA system in which O i and C ii are spread over ∼1050 km s−1 are [P/H]=-0.64, [Zn/H]=-0.74 and [S/H]=-0.82 relative to solar. The sub-DLA system at zabs=1.96753 has [P/H]>0.06, [Zn/H]>-0.02 and [S/H]>-0.18. The overall molecular fraction is in the range -2.7<log f<-0.6, which is the highest value found for DLA systems. H2 is detected in four components at −615, −480, 0 and 85 km s−1 relative to the strongest component at zabs=1.97296. CO is not detected [log N(CO)/N(H i)<-8] and HD could be present at zabs=1.97380. We show that the presence of H2 is closely related to the physical conditions of the gas: high particle density together with low temperature. The observed excitation of high J H2 levels and the molecular fraction show large variations from one component to the other suggesting that the UV radiation field is highly inhomogeneous throughout the system. Gas pressure, estimated from C i absorptions, is larger than what is observed in the ISM of our Galaxy. This, together with the complex kinematics, suggests that part of the gas is subject to high compression owing to either collapse, merging and/or supernovae explosions. This is probably a consequence of intense star formation activity in the vicinity of the absorbing gas.